The Development of Alternative Assessment Instrument in Web-Based Scientific Communication Skill in Science Education Seminar Course - Hardianti, R. D.; Taufiq, M.; Pamelasari, S. D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Science Education Seminar course aims to develop the communication skill of students. The materials and assignments are given to train how to communicate effectively both written and orally. The tasks consist of the scientific papers analysis, conceptual article draft, and other assignments. It took longer time to assess those assignments with only pencil and paper methods therefore a web-based alternative assessment was designed to assess the assignments. Web-based alternative assessment (e-assessment) can facilitate students and lecturer in the process of collecting and assessing tasks. The validation score by the assessment expert of the four aspects resulted 94,64%, 92,86%, 91,07%, and 92,86% meanwhile the score of expert information systems was 90, 63%. Thus the product can be said as valid in very feasible category with the average score of 81.5%. The percentage of positive responses of students was 84,43% that indicates the product is effective to help students and lecturers in the assessing students’ assignment and performance. Therefore, it can be said that the research has met the indicator of feasibility to result a valid and effective product.